SKALA USAHATANI JERUK KEPROK SOE DI KECAMATAN MOLLO UTARA KABUPATEN TIMOR TENGAH SELATAN - Ferdy A. I. Fallo; Krisna Setiawan (Politeknik Pertanian Negeri Kupang, 2009)
SoE Keprok Orange Farming Scale At District Mollo North Regency Timor Tengah Selatan. Elegibility aspect of farming according to scale ownership of till now has not got attention in research, though the aspect so important to be analysed, because through feasibility analysis farming according to knowable ownership scale of cleanness acceptance receiving, investment rate of return and ratio benefit-cost and level of elegibility of investment in each scale ownership of farmingPurpose of this research is description to image of investment, expense and acceptance receiving farming, according to scale ownership and analyse level of elegibility of farming according to ownership scale.Result of research indicates that evaluated from criterion NPV and B/C Ratio, farming Jeruk Keprok SoE, good of small scale, competent big and middle financially. This thing is proved with Nilai NPV > 0 namely each of 6.922.899,64.507.982, and 86.548.418. While Assessing B/C Ratio > 1 for third of scale farming Keprok Orange, namely each of 8, 10, and 8Keywords: farming scale, SoE keprok orange